2020
DOI: 10.1016/j.xplc.2020.100027
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic Insights into Deep Phylogeny of Angiosperms Based on Broad Nuclear Gene Sampling

Abstract: Angiosperms (flowering plants) are the most diverse and species-rich group of plants. The vast majority (∼99.95%) of angiosperms form a clade called Mesangiospermae, which is subdivided into five major groups: eudicots, monocots, magnoliids, Chloranthales, and Ceratophyllales. The relationships among these Mesangiospermae groups have been the subject of long debate. In this study, we assembled a phylogenomic dataset of 1594 genes from 151 angiosperm taxa, including representatives of all five lineages, to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
84
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 70 publications
18
84
3
Order By: Relevance
“…This could be due to the early-divergence of order Ranunculales from all the other core eudicots. Order Ranunculales is considered as an early-diverging eudicot order and is among a few other eudicot orders (collectively known as basal eudicots) that are found to be sister lineage to the core eudicots [52,64,65], which was also observed in the case of T. cordifolia that showed early divergence from all other dicot species (Figure 2). Thus, the early divergence could be the reason for its distinct position relative to the other eudicots and monocot species.…”
Section: Discussionmentioning
confidence: 82%
“…This could be due to the early-divergence of order Ranunculales from all the other core eudicots. Order Ranunculales is considered as an early-diverging eudicot order and is among a few other eudicot orders (collectively known as basal eudicots) that are found to be sister lineage to the core eudicots [52,64,65], which was also observed in the case of T. cordifolia that showed early divergence from all other dicot species (Figure 2). Thus, the early divergence could be the reason for its distinct position relative to the other eudicots and monocot species.…”
Section: Discussionmentioning
confidence: 82%
“…As genus-level sampling becomes increasingly complete—a target that is well within reach—this backbone will substantially increase our ability to study the dynamics of plant diversity over time and revisit long-standing questions in systematics (Magallón et al 2018; Sauquet and Magallón 2018; Soltis et al 2019). Importantly, it will also sharpen the focus on truly intractable phylogenetic problems (Yang et al 2020; Zhao et al 2020), encouraging the exploration of the biological drivers of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing (HTS) now promises to significantly deepen our understanding of evolutionary relationships among Earth’s species, including angiosperms (Li et al 2019; Yang et al 2020). For example, the One Thousand Plant Transcriptomes (1KP) initiative has brought an unprecedented scale of data to bear on the plant tree of life (Wickett et al 2014; Gitzendanner et al 2018; Leebens-Mack et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Oxalidales belongs to the ‘COM clade’, which also includes Celastrales and Malpighiales and has been broadly recognized as a well-defined monophyletic group ( APG IV, 2016 ; Valencia-D et al., 2020 ). Nevertheless, several recent studies based on nuclear genes suggested contradictory relationships ( Zhao et al., 2016 ; Zeng et al., 2017 ; Yang et al., 2020 ). Despite support for monophyly of each of the orders within COM, the phylogenetic relationships among the orders of this group remain ambiguous ( APG IV, 2016 ; Valencia-D et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%